Learning and teaching clinical communication in the clinical workplace. (31st July 2015) - Brown, Jo; Dearnaley, Jo
Summary: Background: Clinical communication teaching and learning has become increasingly separate from the clinical workplace over the last 20 years in the UK, and in many medical schools is front‐loaded to the early years of the curriculum. Many reasons exist to explain this separation, including the increasing use of simulation. However, learning by simulation alone is not ideal, and the literature now points towards a new direction that blends simulation with authentic experiences in the clinical workplace to aid the transition to clinical life. Context: This article presents a practical example of collaboration between a London medical school and a hospital trust to provide an integrated clinical communication learning experience for students by situating teaching on the clinical wards for senior medical students. Clinical communication teaching and learning has become increasingly separate from the clinical workplace Innovation: We outline a new teaching initiative, the 'Communication on the wards' pilot project, that blends clinical communication teaching with ward‐based learning in an authentic environment, with patients, medical students and teachers working together. Implications: This teaching initiative was a practical attempt to bridge the theory–practice gap in clinical communication education, and to place learning in the clinical workplace for students. As such, it was enjoyed by all those who took part, and may be the way forward for clinical communication teaching and learning in the future.